Caries-preventive Effect of Supervised Toothbrushing and Sealants. (September 2015) - Hilgert, L.A.; Leal, S.C.; Mulder, J.; Creugers, N.H.J.; Frencken, J.E.
To investigate the effectiveness of 3 caries-preventive measures on high– and low–caries risk occlusal surfaces of first permanent molars over 3 y. This cluster-randomized controlled clinical trial covered 242 schoolchildren, 6 to 7 y old, from low socioeconomic areas. At baseline, caries risk was assessed at the tooth surface level, through a combination of ICDAS II (International Caries Detection and Assessment System) and fissure depth codes. High–caries risk occlusal surfaces were treated according to daily supervised toothbrushing (STB) at school and 2 sealants: composite resin (CR) and atraumatic restorative treatment–high-viscosity glass-ionomer cement (ART-GIC). Low–caries risk occlusal surfaces received STB or no intervention. Evaluations were performed after 0.5, 1, 2, and 3 y. A cavitated dentine carious lesion was considered a failure. Data were analyzed according to the proportional hazard rate regression model with frailty correction, Wald test, analysis of variance, and t test, according to the jackknife procedure for calculating standard errors. The cumulative survival rates of cavitated dentine carious lesion–free, high–caries risk occlusal surfaces were 95.6%, 91.4%, and 90.2% for STB, CR, and ART-GIC, respectively, over 3 y, which were not statistically significantly different. For low–caries risk occlusal surfaces, no statistically significant difference was observed between the cumulative survival rate of the STB group (94.8%) and the no-intervention group (92.1%) over 3 y. There was neither a difference among STB, CR, and ART-GIC on school premises in preventing cavitated dentine carious lesions in high–caries risk occlusal surfaces of first permanent molars nor a difference between STB and no intervention for low–caries risk occlusal surfaces of first permanent molars over 3 y.